2011
DOI: 10.1186/1471-230x-11-82
|View full text |Cite
|
Sign up to set email alerts
|

Allergic proctocolitis refractory to maternal hypoallergenic diet in exclusively breast-fed infants: a clinical observation

Abstract: BackgroundAllergic proctocolitis (APC) in exclusively breast-fed infants is caused by food proteins, deriving from maternal diet, transferred through lactation. In most cases a maternal cow milk-free diet leads to a prompt resolution of rectal bleeding, while in some patients a multiple food allergy can occur. The aim of this study was to assess whether the atopy patch test (APT) could be helpful to identify this subgroup of patients requiring to discontinue breast-feeding due to polisensitization. Additionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 36 publications
1
36
0
12
Order By: Relevance
“…Lucarelli et al in 2011 found APT to be helpful in identifying those infants who required extensively hydrolyzed formula due to persistent symptoms despite elimination of the most common inciting foods. However, this study was small (14 infants) and without controls for comparison; further study is need to validate these findings [47].…”
Section: Diagnosismentioning
confidence: 59%
See 1 more Smart Citation
“…Lucarelli et al in 2011 found APT to be helpful in identifying those infants who required extensively hydrolyzed formula due to persistent symptoms despite elimination of the most common inciting foods. However, this study was small (14 infants) and without controls for comparison; further study is need to validate these findings [47].…”
Section: Diagnosismentioning
confidence: 59%
“…In a study including 95 breastfed infants, stools normalized with sequential elimination of potential triggers from the maternal diet as follows: 65 % improved with elimination of cow's milk, 19 % with egg, 6 % with corn, and 3 % with soy [5].Five percent of infants were sensitized to multiple foods [5]. There are reports of infants with persistent symptoms despite removal of the above-mentioned foods; these infants' stools have improved on extensively hydrolyzed formula, suggesting that there are likely other inciting foods in FPIAP that have not yet been identified [47,63].…”
Section: Inciting Foodsmentioning
confidence: 83%
“…Se excluyeron historias clínicas de lactantes que no tuvieron prueba de eliminación y provocación abierta o que hubieran consultado por otras causas: síndrome de malabsorción, enfermedades metabólicas, hepáticas, renales, etc. 1,[3][4][5][6][7][8]10,[16][17][18][19][20]22,23,25,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] .La Información de las historias clínicas, fue recolectada del sistema de información HIS-ISIS ® del HU-FSFB y MEDSYS V4.0 ® de la Asociación Médica de los Andes (AMA), en un cuestionario. Se realizó una prueba piloto en 10 pacientes.…”
Section: Pacientes Y Métodounclassified
“…Debido al paso placentario, en los niños altamente sensibles puede ser necesario que la madre evite el consumo de leche y sus derivados para evitar suministrar péptidos de la leche de vaca al lactante a través de la leche materna (39). También se debe considerar la necesidad del suministro de vitamina D y de calcio de manera individualizada.…”
Section: Consideraciones En Menores De Dos Añosunclassified